"Quivered Out of Decimals": Simulating Somatime in Emily Dickinson's Entropic Text. (2nd September 2017) - Rabinowitz, Ivan
ABSTRACT: In desiring to constitute herself independently of any unitary subject, Emily Dickinson apostrophises—and simulates—the aberrant complexities of mortality. Her texts— closed systems within which grammatical and semantic conventions are atomised by ellipsis and parataxis—calibrate measures of disorder which signal irreversible changes in consciousness, perception, and experience. By bringing Emily Dickinson's intellectual and sensuous cognition of mortality into prominence as an exemplary instance of somatime in the entropic text, the article explores some of the ways in which the representation of mitotic time and pineal embodiment is adapted and transformed through the figural potentiality of poetic language.